Apollon Mark: bounce mark visualization system for ball sports judgement using prediction-based preceding mirror control - Himari Tochioka; Tomohiro Sueishi; Masatoshi Ishikawa (SICE Journal of Control, Measurement, and System Integration)
Video Assistant Referee (VAR) is used for line judging in tennis to improve the fairness of a game. However, currently, popular VAR systems are based on three-dimensional trajectories and do not take actual ball bounce marks into account, which may lead to misjudgment due to misalignment. Therefore, in this paper, we propose Apollon Mark, a bounce mark visualization system with preceding mirror control based on high-speed drop location prediction. Based on high-speed measurement of three-dimensional position and motion prediction, the proposed system enables a high-resolution camera to capture the ground texture both before and after the ball drops on the ground by directing the angle of view of the camera to the predicted drop location of the ball before it drops. The system then enables bounce mark visualization by simple differential processing between the before and after images with a template-matching image processing algorithm. We have quantitatively evaluated the validity of the proposed system through the simulation of drop location prediction for real-scale tennis ball trajectories and validated the bounce mark visualization algorithm under a dynamic angle of view using galvanometer mirrors.